2020
DOI: 10.31770/2561-7516.1062
|View full text |Cite
|
Sign up to set email alerts
|

Analyse du contexte clinique dans le développement et l’implantation d’une intervention de soutien pour les familles de patients atteints de lésions cérébrales acquises : une étude qualitative

Abstract: Mots-clés lésion cérébrale; famille; intervention familiale; étude qualitative; facteurs contextuels Résumé Introduction : Les lésions cérébrales acquises (LCA) sont parmi les principales causes d'invalidité chez les adultes. Soutenir les familles des patients atteints de LCA fait partie des bonnes pratiques, mais cela n'est pas systématique en Suisse. En prévision de l'implantation d'une nouvelle intervention familiale, une analyse des facteurs contextuels a été effectuée. Objectifs : Cette étude avait pour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The results of our qualitative exploratory study showed four main categories (family system, health care system, collaboration, and care context) that are closely related to each other and fifteen sub-categories (de Goumoëns et al, 2020). The HCPs highlighted the importance of environmental factors (care context; architecture, location and moments of formal and informal meetings with families), as well as interpersonal factors (interdisciplinary collaboration and multidisciplinary collaboration).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The results of our qualitative exploratory study showed four main categories (family system, health care system, collaboration, and care context) that are closely related to each other and fifteen sub-categories (de Goumoëns et al, 2020). The HCPs highlighted the importance of environmental factors (care context; architecture, location and moments of formal and informal meetings with families), as well as interpersonal factors (interdisciplinary collaboration and multidisciplinary collaboration).…”
Section: Resultsmentioning
confidence: 92%
“…We conducted an analysis of the contextual factors that could influence the feasibility of our newly developed intervention, using an exploratory qualitative approach (Gray et al, 2017). The full report is presented elsewhere (de Goumoëns et al, 2020). We conducted eight semi-structured interviews, with nurses and allied health professional managers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations